SCIENTIFIC AND PEDAGOGICAL FOUNDATIONS OF TRAINING HIGHLY QUALIFIED PARA-ATHLETIC THROWERS - Abdiyev Sherzod Abdirakhmonovich (Sciental Journals Publishing, 2025)
This scientific work investigates the scientific and pedagogical foundations of training highly qualified para-athletic throwers. During the research, existing theoretical sources were analyzed, and a training program adapted to the physical, technical, and psychological preparedness of para-athletes was developed. The experimental implementation of this program showed a significantly positive effect on athletes' performance results, movement coordination, and technical skills.
Keywords: Para-athletics, throwing disciplines, highly qualified athlete, training program, physical preparedness, technical skill, pedagogical methodology, adaptive sport, athletes with disabilities, experimental analysis.